2015
DOI: 10.1093/jrr/rrv001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adverse effects of proton and X-ray chemoradiotherapy for esophageal cancer using an adaptive dose–volume histogram analysis

Abstract: Cardiopulmonary late toxicity is of concern in concurrent chemoradiotherapy (CCRT) for esophageal cancer. The aim of this study was to examine the benefit of proton beam therapy (PBT) using clinical data and adaptive dose–volume histogram (DVH) analysis. The subjects were 44 patients with esophageal cancer who underwent definitive CCRT using X-rays (n = 19) or protons (n = 25). Experimental recalculation using protons was performed for the patient actually treated with X-rays, and vice versa. Target coverage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…Although randomized clinical trials are necessary to confirm whether proton therapy reduces toxicity as compared with photon therapy, it is hard to perform such studies. NTCP modeling analysis is one method to estimate the effectiveness of proton over photon radiotherapy from previous studies [29][30][31]. NTCP of rectum and sigmoid were calculated based on LKB model.…”
Section: Discussionmentioning
confidence: 99%
“…Although randomized clinical trials are necessary to confirm whether proton therapy reduces toxicity as compared with photon therapy, it is hard to perform such studies. NTCP modeling analysis is one method to estimate the effectiveness of proton over photon radiotherapy from previous studies [29][30][31]. NTCP of rectum and sigmoid were calculated based on LKB model.…”
Section: Discussionmentioning
confidence: 99%
“…Jakobi et al conducted in silico study using NTCP modeling analysis in head and neck region to identify patients who may benefit from PBT [31][32][33]. Makishima et al showed that NTCP value for the lung and heart decreased in proton plan compared with photon plan in esophageal cancer [34]. Toramatsu et al showed that large size of hepatocellular carcinoma could be more safely treated with SSPT than IMRT regarding the risk of radiation-induced liver disease using NTCP modeling analysis [35].…”
Section: Discussionmentioning
confidence: 99%
“…Makishima et al compared the dose distribution of X-ray beam RT and PBT for esophageal cancer patients (53), and found that cardiac and pulmonary toxicities were correlated with the radiation doses to heart and lung. The toxicities could be markedly reduced by the use of PBT, based on analysis using normal tissue complication probability.…”
Section: Esophageal Cancermentioning
confidence: 99%